2016
DOI: 10.1002/hed.24178
|View full text |Cite
|
Sign up to set email alerts
|

Surgical prophylaxis with gram‐negative activity for reduction of surgical site infections after microvascular reconstruction for head and neck cancer

Abstract: Alcohol use, longer surgical duration, and lack of gram-negative postoperative prophylactic coverage are modifiable risk factors for surgical site infection development. © 2016 Wiley Periodicals, Inc. Head Neck 38: First-1454, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 28 publications
6
42
2
Order By: Relevance
“…28 The investigators found a lower incidence of SSI among patients who received ampicillin/sulbactam versus clindamycin (13% vs 27%, P = .02). While these findings were demonstrated in a number of additional studies, 4,19,29 some investigators found no difference in SSI when using GN POABP and not. [30][31][32][33][34][35][36] Many of these data focus on clindamycin POABP as a significant risk factor for SSI, suggesting that GN coverage leads to better patient outcomes.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…28 The investigators found a lower incidence of SSI among patients who received ampicillin/sulbactam versus clindamycin (13% vs 27%, P = .02). While these findings were demonstrated in a number of additional studies, 4,19,29 some investigators found no difference in SSI when using GN POABP and not. [30][31][32][33][34][35][36] Many of these data focus on clindamycin POABP as a significant risk factor for SSI, suggesting that GN coverage leads to better patient outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3] SSIs in this setting are associated with poor outcomes, including prolonged hospitalizations, development of additional health care-associated infections, and death. [2][3][4] While advancements in head and neck reconstruction have continued to develop, there remain few data identifying modifiable risk factors for SSI prevention. [5][6][7][8][9][10] Antibiotic prophylaxis has reduced the incidence of SSI in patients who have undergone extensive surgical revision of the head and neck, [11][12][13][14] but current surgical infection prophylaxis guideline recommendations may fail to account for the complexity of microvascular reconstruction relative to other head and neck procedures regarding spectrum and duration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Available data related to the use of extended spectrum prophylaxis targeted to multidrug resistant pathogens, such as multidrug resistant S aureus (MRSA) and P aeruginosa , are limited. Both organisms are listed as CDC major health threats and have the capability to colonize the skin, respiratory tract, and prosthetic material used for surgical revision or infusion of IV chemotherapy agents (eg, tracheostomy or indwelling central venous catheters) . Although the incidence of these organisms in SSI is questionable or underreported, the perceived risk and detrimental effects these organisms have on patient outcomes contribute to antibiotic misuse by clinicians …”
Section: Statementsmentioning
confidence: 99%
“…The application criteria in the study by Pool et al [17] were similar to the diagnostic criteria of deep incisional SSI. In only one study by Wagner et al [18], SSIs were classified as superficial or deep. Notably, in three studies, orocutaneous fistula that did not meet the CDC criteria was not categorized as a SSI [3,17,19].…”
Section: Resultsmentioning
confidence: 99%